Late-Victorian Girls and their Manuscript Magazines - Burke, Lois. author. aut Link
XI, 136 p. 15 illus., 8 illus. in color.
Keywords: “This book is engaging and well-written, and it makes an original contribution to our understanding of Victorian girlhood in the last decades of the nineteenth century and manuscript magazine culture during this period. Burke is an expert in this field, and she marshals these interesting and relatively unknown materials in intriguing ways to discuss girls and their contributions to literary culture through manuscript publications.” —Kristine Moruzi, Associate Professor in Literary Studies, Deakin University, Australia This open access book presents fresh archival evidence to explore the underexamined manuscript cultures of girls living in Britain in the late nineteenth century. Girls were keen writers during this period, which witnessed Golden Ages of children's literature and journalism, as well as major developments in proto feminism. Girl writers were particularly prolific in the writing of manuscript magazines. These were handmade magazines in which the contributors were also the readers and subscribers. This book presents three case study chapters exploring manuscript magazines which were created and exchanged amongst girl-led writing groups and within families, and references many other examples of manuscript magazine cultures from the late-Victorian period. It argues that strategies of transformative writing—namely appropriating literary texts—often characterized girls' contributions to manuscript magazines. Lois Burke is Assistant Professor of Critical Heritage, Innovation, and Curation at Tilburg University, The Netherlands. She teaches and publishes on children's literature, Victorian studies, life writing, Scottish literature, and cultural heritage. .